ANALYSIS OF DECISION MAKING INVESTMENT IN SHARES OF NON-BUMN BANKING COMPANIES USING THE CAPITAL ASSET PRICING MODEL (CAPM) METHOD - Silvi Madani; Yovita Vivianty Indriadewi Atmadjaja; Endri Purnomo (CV. Radja Publika, 2024)
A stock investment depends on the potential investor's accuracy in finding and processing information to help make investment decisions and determine how much risk and profit can be obtained in the future. The aim of this research is to analyze stock risks and returns as well as stock investment decisions using the CAPITAL ASSET PRICING MODEL (CAPM) method on shares in the banking sector listed on the Indonesia Stock Exchange in 2020-2022. This research uses a type of descriptive research with a quantitative approach using secondary research data in the form of monthly closing stock prices (Closing Price), monthly Composite Stock Price Index (IHSG) and monthly SBI interest rate (BI Rate). The population in this research are companies in the banking sector listed on the Indonesia Stock Exchange in 2020-2022. The number of samples in this study was 37 shares. The sampling technique in this research used purposive sampling. The data collection method in this research uses the documentation method. The data analysis technique used is the CAPITAL ASSET PRICING MODEL (CAPM) method. The research results show that of the 37 companies sampled, there are twenty-five (25) stocks that are classified as efficient or undervalued because they have an individual rate of return (Ri) that is greater than the expected rate of return. Shares that are classified as efficient are: AGRO, AGRS, ARTO, BABP, BBCA, BBHI, BBKP, BBYB, BGTG, BINA, BJTM, BJBR, BKSW, BMAS, BNBA, BNGA, BNII, BNLI, BRIS, BSIM, BVIC, INPC, PNBS, PNBN, NOBU, then the recommended decision for investors is to buy shares and there are twelve (12) shares which are classified as inefficient or overvalued shares because the individual return (Ri) is smaller than the expected rate of return. Shares that are classified as inefficient are: BBMD, BDMN, BEKS, BTPN, BTPS, DNAR, MAYA, MCOR, SDRA, NISP, MEGA, BACA, so the investment decision recommended to investors is to sell shares.